Unravelling the Pharmacological and Nutritional Potential of Kiwifruit for Human Health: A Comprehensive Review - , Duyu Monya; , Barun Singh; , B. N. Hazarika; , L. Wangchu; , P. Sarma; , Amit Kumar Singh; , N. Bidyaleima Chanu (Archives of Current Research International, 2025)
Kiwifruit (Actinidia deliciosa) belongs to the family Actinidiaceae, and the genus Actinidia is a highly nutritious fruit abundant with essential vitamins, minerals, polyphenols, flavonoids, and the unique enzyme actinidin, which aids digestion. These components contribute to kiwifruit’s role as a functional food with significant therapeutic potential. Kiwifruit supports various physiological functions, including immune enhancement, cardiovascular health, and digestive regulation. Its rich fiber content promotes gut microbiota growth, improving digestion and reducing constipation. The presence of polyphenols, carotenoids (lutein, zeaxanthin), and flavonoids strengthens antioxidant defenses, reduces inflammation, and helps prevent chronic diseases such as cardiovascular disorders, neurodegenerative conditions, and metabolic syndrome. The low fiber content makes it beneficial for blood sugar regulation, aiding in diabetes management. The actinidin enzyme present in kiwifruit makes it particularly beneficial for individuals with digestive disorders by enhancing protein digestion and nutrient absorption. Additionally, its prebiotic properties foster the growth of beneficial gut bacteria, contributing to better digestive and immune health. Kiwifruit is rich in antioxidants and also supports skin health by promoting collagen synthesis, reducing oxidative stress, and maintaining hydration. Emerging research highlights its potential neuroprotective effects, suggesting a role in reducing cognitive decline and oxidative stress in the brain. Its cardioprotective properties help regulate blood pressure, and improve vascular function. With applications in functional foods, nutraceuticals, and pharmaceuticals, kiwifruit continues to gain attention for its preventive healthcare potential. Incorporating kiwifruit into the diet provides a natural approach to enhancing overall well-being, making it a valuable component in promoting longevity and reducing the risk of chronic diseases. This review seeks to provide a comprehensive knowledge of kiwifruit's nutritional profile, bioactive properties, therapeutic potential, and commercial importance, offering scientifically backed recommendations for individuals.